TINJAUAN YURIDIS KETIDAK PATUHAN PEJABAT NEGARA TERHADAP PUTUSAN PENGADILAN TATA USAHA NEGARA (Studi Kasus Dalam Perkara No. 2/G/2022/PTUN.JPR) - Marwah Marwah; Safiuddin Safiuddin (Institut Agama Islam Negeri Fattahul Muluk Papua, 2026)
State Administrative Court decisions that have permanent legal force must be implemented by state officials, as stipulated in Law No. 5 concerning the PTUN and Law No. 30 of 2014 concerning Government Administration. However, in case No. 2/G/2022/PTUN.JPR, the decision has not been implemented by the officials concerned. This indicates non-compliance with court decisions. Therefore, this study aims to analyze the factors of officials' non-compliance with PTUN decisions and analyze the PTUN's efforts to encourage the implementation of decisions. This study uses a normative-empirical juridical approach to examine the implementation of legal provisions in practice, with data obtained through literature studies, document studies, and interviews. The results of the study indicate that factors for non-compliance with decisions are due to a lack of legal awareness and unclear sanctions. The efforts made by the Jayapura PTUN in encouraging the implementation of decisions are in accordance with applicable execution regulations, however, due to the limited authority of the PTUN, which only acts as a supervisor of decisions, there are no direct coercive measures. This situation indicates that court decisions have not been implemented effectively and still face obstacles that could potentially harm public rights. To improve official compliance with decisions, it is recommended to establish an executive body, strengthen sanctions stipulated in laws and regulations, increase legal awareness through regular education and guidance, and transparently monitor the implementation of court decisions.